Systemic risk elicitation: Using causal maps to engage stakeholders and build a comprehensive view of risks - Ackermann, Fran; Howick, S.; Quigley, J.; Walls, L.; Houghton, Tom (Elsevier BV * North-Holland, 2014)
As evidenced through both a historical and contemporary number of reported over-runs, managing projects can be a risky business. Managers are faced with the need to effectively work with a multitude of parties and deal with a wealth of interlocking uncertainties. This paper describes a modelling process developed to assist managers facing such situations. The process helps managers to develop a comprehensive appreciation of risks and gain an understanding of the impact of the interactions between these risks through explicitly engaging a wide stakeholder base using a group support system and causal mapping process. Using a real case the paper describes the modelling process and outcomes along with its implications, before reflecting on the insights, limitations and future research.